Development of rice washing machine (warima) - Ismail, Yunus (2024)
In this globalisation era, food’s hygiene is the most important aspect before the food get cook or eaten by human. Before this, washing rice manually by hands was really a time-consuming and energy waste for human. However, rice washing machine at the restaurants are too big in size and seemly cannot fit into small countertop. As a result, having rice washing machine that is small and can wash the rice for at least 4 people is a win and allowing human to achieve the best productivity and food quality. To design a machine that is capable of handling food with smaller size, research must be made beforehand. The prototype of the machine has been successfully fabricated according to the design based on the Solidworks and the result was good. It functioned well without any failure. As conclusion, the prototype will gain more improvements based on the panel’s comments and suggestions